Impact of non‐binding FDA guidances on primary endpoint selection in Alzheimer's disease trials. Issue 1 (24th March 2022) - Yu, Jeffrey C.; Hlávka, Jakub P.; Joe, Elizabeth; Richmond, Frances J.; Lakdawalla, Darius N.
Abstract: Introduction: The U.S. Food and Drug Administration (FDA)'s guidances help describe the agency's current thinking on regulatory issues and serve as a means of informal policymaking that is non‐binding. This study examines the impact of two guidance documents for Alzheimer's disease (AD) trials. The first guidance in 2013 encouraged the use of cognitive/functional endpoints, while the second in 2018 modified such recommendation. Methods: Using pivotal trial data, we applied a regression discontinuity in time (RDiT) framework to examine trialist response to these guidance documents. Results were stratified by disease‐modifying therapy (DMT) status, and controlled for disease staging, FDA registration status, and trial phase. Results: Among AD DMT trials, annual use of cognitive/functional composite endpoints significantly increased after the 2013 guidance (+12.9%, P < .001), and significantly decreased after the 2018 guidance (–19.9%, P = .022). Discussion: Although guidance documents do not set new legal standards or impose binding requirements, our findings indicate they are broadly followed by AD trialists.